Analisis Kinerja Guru Penggerak di SD Negeri 149 Palembang - Sari, Dwi Kartika (Yayasan Sembilan Pemuda Indonesia, 2024)
This research discusses the role of teacher leader in improving the quality of education and student learning outcomes. This research uses a qualitative method where this method uses interview techniques, observation and document analysis. This data collection uses a population of all teachers significantly contributes to the implementation of innovative teaching practices, the development of student potential and the formation of collaborative professional learning communities. Apart from that this research analyses the importance of teacher leader in increasing student involvement and create a safe and comfortable learning environment. This research has identified several challenges that will be faced including limited resources, time, the need for continuous training to improve competency. This is recommended so that schools can provide ongoing support and opportunities for professional development for teacher leader. Overall, the performance of teacher leader at SD Negeri 149 Palembang can play a crucial role, so that the school’s educational goals can be achieved which can provide benefits to the student’s learning experience.